Ifjúságkutatások Ukrajnában és Kárpátalján - Csernicskó István; Черничко Степан; Csernicsko Istvan; Hires-László Kornélia; Гіреш-Ласлов Корнелія (Mathias Corvinus Collegium-Tihanyi Alapítvány és a Magyar Tudományos Akadémia Társadalomtudományi Kutatóközpont Kisebbségkutató Intézet, 2017)
Írásunk két nagyobb részből áll. Az elsőben röviden áttekintjük az ukrajnai ifjúságkutatásokat, bemutatjuk főbb témaköreiket, illetve azokat a kutatóműhelyeket, amelyek ilyen jellegű vizsgálatokkal (is) foglalkoznak. A második részben Kárpátaljára, a Kárpátalja területén végzett, a kárpátaljai magyar fiatalokat érintő ifjúságkutatások bemutatására koncentrálunk. Tanulmányunknak nem célja az említésre kerülő kutatások mintavételi eljárásainak, módszertanának, illetve eredményeinek és következtetéseinek részletes bemutatása és értelmezése, elemzése. Célunk az, hogy az olvasó tájékozódhasson arról, melyek az ukrajnai és kárpátaljai ifjúságkutatás legfőbb témái, mely tudományos műhelyek foglalkoznak e kérdéssel, és az érdeklődők támpontokat kaphassanak ahhoz, hol keressék az ukrajnai, kárpátaljai (magyar) ifjúsággal foglalkozó kutatásokról szóló elemzéseket, beszámolókat.

Abstract. The study briefly presents research institutes dealing with Ukrainian youth research. The authors describe how the Ukrainian sociology and state define the notion of “youth”. The study presents the most important studies on youth problems and issues. The paper consists of two major parts. The first one briefly reviews research projects on Ukrainian youth, presenting the main topics, and the research institutes that deal with such studies. It discusses the activities of the Institute of Sociology of the National Academy of Sciences of Ukraine and finds that the research projects of the institution do not pay particular attention to studying the youth. On the other hand, the M. Ptoukha Institute for Demography and Social Studies, which is also part of the Ukrainian Academy of Sciences, provides a comprehensive analysis on youngsters on the basis of statistics and questionnaire surveys. The non-academic related Ukrainian Institute of Social Research carries out research and analysis aimed at young people, including international research projects. We also present the results of a research project carried out by Gorshenin Institute for Non-Profit Analysis and Research Centres focusing on college students and university students. We also report on a survey ordered by the Ministry of Youth and Sports of Ukraine in 2015.The second part of the paper concentrates on the presentation of youth research in Transcarpathia. The research on Hungarians in Transcarpathia was first and foremost related to surveys in the Carpathian Basin aimed at the Hungarian population, such as MOZAIK 2001, 2011, 2016. Other surveys have also been organized and carried out primarily under the guidance of a research institute in Hungary. We also present surveys related to young people living in Transcarpathia, which were carried out by non-Transcarpathian researchers. On a local level, only such types of research can be found that are targeting only certain segments of youngsters. The study is not intended to describe, interpret or analyse the sampling procedures, methodology, results and conclusions of the surveys mentioned above.
Youth research in Ukraine and Transcarpathia
Keywords: ifjúságkutatás; kutatóműhelyek; Kárpátalja; Ukrajna